Women policing across the globe: shared challenges and successes in the integration of women police worldwide - Rabe-Hemp, Cara E. (Rowman & Littlefield, 2020)
Provides a cross-cultural comparison of the integration of women in policing across the globe, paying special attention to the unique contributions that women make to the field, along with the shared challenges and resistance they face. Individual chapters within the book provide students with a snapshot of the status of women in modern police agencies in the countries of the United States, Kuwait, China, the United Kingdom, Australia, the United Arab Emirates, and Taiwan. However, shared issues and successes of women police in many more countries worldwide are discussed throughout the entire book. Contributors explore the different origins of entry, specialized roles, experiences of resistance, and effects of historical events that have shaped the experiences of modern women police from across the world. The authors discuss the new gains women are making, despite the obstacles they face, and ways they are transforming how policing is done every day. --From publisher description